Eugenics and racial anthropology in the Ukrainian radical nationalist tradition. Issue 1 (24th May 2019) - Rudling, Per Anders
Argument: Eugenics and race played significant roles in Ukrainian interwar nationalism, yet remain largely unstudied. The Ukrainian nationalists' understanding of the racial makeup of their imagined community was contradictory as they struggled to reconcile their desire for racial "purity" with the realities of significant variations between the populations inhabiting the enormous territories which they sought to include in their intended state project. The "turn to the right" over the 1930s placed an increased onus on race, and eugenics came to occupy an increasingly prominent place in Ukrainian radical nationalism from around 1936. In 1941, the leading Ukrainian far-right organization, the OUN had developed a project for eugenic engineering, for their aborted state, declared in L'viv on June 30, 1941. Racial conceptualizations of the Ukrainian community figured prominently well into the Cold War era, gaining a new actuality and meaning in an émigré community dispersed across several countries.